Role of STAT3 and vitamin D receptor in EZH2‐mediated invasion of human colorectal cancer. Issue 3 (7th June 2013) - Lin, Yan‐Wei; Ren, Lin‐Lin; Xiong, Hua; Du, Wan; Yu, Ya‐Nan; Sun, Tian‐Tian; Weng, Yu‐Rong; Wang, Zhen‐hua; Wang, Ji‐Lin; Wang, Ying‐Chao; Cui, Yun; Sun, Dan‐Feng; et al.
Abstract: The polycomb group protein enhancer of zeste homologue 2 ( EZH2 ), which has histone methyltransferase (HMT) activity, is overexpressed in malignant tumours. However, the role of EZH2 in colorectal cancer (CRC) invasion is little known. Here we investigated the clinical significance, biological effects, and mechanisms of EZH2 signalling. Knockdown of EZH2 significantly reduced cell invasion and secretion of matrix metalloproteinases 2/9 (MMP2/9) in in vitro studies. Knockdown of EZH2 dramatically increased overall survival and decreased metastasis of lung in in vivo studies. Conversely, overexpression of EZH2 significantly increased lung metastasis and shortened overall survival when compared with control tumours. EZH2 ‐induced CRC cell invasion may depend on down‐regulation of vitamin D receptor (VDR), which is considered to be a marker of CRC invasion. EZH2 regulates the histone trimethylation of lysine 27 (H3K27me3) in the VDR promoter. Moreover, we found that STAT3 directly binds to the EZH2 promoter and regulates VDR down‐regulation in CRC cells. Significant inverse correlations were observed between the expression of EZH2 and pSTAT3 and that of VDR in CRC tissues compared with normal tissue in patients. We show the role of EZH2 in CRC metastasis and identify VDR as a target gene of EZH2 . EZH2 expression may be directly regulated by STAT3, and STAT3 may play an important role in EZH2 ‐mediated VDR down‐regulation in CRC. This pathway may provide potential targets in aggressive CRC. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.